The Western Ideology and Other Essays - Gamble, Andrew (Book collections on Project MUSE., 2021)
The Western Ideology brings together for the first time Andrew Gamble's writings on political ideas and ideologies, which illustrate the main themes of his writing in intellectual history and the history of ideas, including economic liberalism and neoliberalism, and critiques from both social democratic and conservative perspectives.